2000
DOI: 10.1143/jjap.39.745
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Crystallization Behavior of Sputter-Deposited Nitrogen-Doped Amorphous Ge2Sb2Te5 Thin Films

Abstract: The crystallization behavior of nitrogen-doped amorphous Ge 2 Sb 2 Te 5 -(N) phase-change thin films was studied by utilizing differential scanning calorimetry, in situ ellipsometry and in situ transmission electron microscopy. The combined analysis of in situ ellipsometry isotherms of amorphous Ge 2 Sb 2 Te 5 -(N) films and the Johnson-Mehl-Avrami equation revealed that the crystallization process of amorphous Ge 2 Sb 2 Te 5 -(N) films changes depending on the nitrogen content. The crystallization behavior of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(36 citation statements)
references
References 5 publications
4
32
0
Order By: Relevance
“…The curves of the samples annealed for 60 and 120 min almost overlapped each other, which means the saturation of optical constants has occurred at or before a 60 min thermal treatment time. Thus, the amount of crystallization can be calculated by monitoring the change of C or D values [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The curves of the samples annealed for 60 and 120 min almost overlapped each other, which means the saturation of optical constants has occurred at or before a 60 min thermal treatment time. Thus, the amount of crystallization can be calculated by monitoring the change of C or D values [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in situ or ex situ monitoring of film crystallizations by ellipsometry have been presented [8,[11][12][13][14]. Plots of measured tan C (the amplitude ratio of the reflection coefficients of p-and s-polarized lights) and cos D (the phase difference between the two polarized lights) values against annealing time show typical S-shaped transformation curves [13]. In addition, SE has the advantages of requiring a short measurement time (about 10 min) and being non-destructive.…”
Section: Introductionsmentioning
confidence: 99%
“…(b) Fig 6. The calculated resistances versus different applied currents Simulation results show the ratio of reset to set state resistance is ≈800.…”
mentioning
confidence: 97%
“…For the effects of heater's aspect ratio, it is found that the effect of the heater's thickness on the temperature is more evident than its height. The effect of doping-dependent electrical conductivity of the GST in crystalline state on the temperature profile of the PCM cell is also discussed [5,6]. One conformal bi-layer GST structure with different electric and thermal conductivities on the GST layers is examined for different applied currents to extract the curve of resistances versus applied currents.…”
mentioning
confidence: 99%
“…In particularly, the addition of nitrogen is known to be effective in modifying phase change behaviors by suppressing crystallization from an amorphous state. [8][9][10][11][12][13][14] The use of such materials with appropriate properties is critically important in PRAM device operations because the nature of the crystalline phase is directly related to device parameters and consequent electrical properties.Despite the previous reports on the advantages of nitrogen doping, most of the conclusions are based upon data obtained under experimental conditions that are different from those in actual PRAM device operations. The most apparent difference is the use of the nitrogen-doped Ge 2 Sb 2 Te 5 (NGST) in an as-deposited amorphous state for the study of the mechanism of crystallization, while the melt-quenched amorphous state is the case in the actual PRAM device operations.…”
mentioning
confidence: 99%